Mothers' experiences of neonatal jaundice: A qualitative study - Masoumeh Mohajer Rahbari; Roghieh Kharaghani; Forouzan Olfati; Afsaneh Sadeghian (Tehran University of Medical Sciences, 2015)
Background & Aim: The importance of neonatal jaundice is not only for its social, economic, and psychological complications resulted from hospitalization of neonates in the hospital, but also for the permanent neurological handicaps and its consequent high morbidity. Since Iranian mothers have no, in spite of the importance of matter, appropriate approach in coping with their newborn jaundice, this study aimed to explore mother's experiences of neonatal jaundice. Methods & Materials: This qualitative study was carried out through in-depth semi-structured interviews with 14 mothers whose infants were hospitalized in one of the hospitals affiliated to Shahrood University of Medical Sciences with a diagnosis of neonatal jaundice. The participants were selected purposefully and the data were analyzed using qualitative content analysis. Results: Two main themes and several subthemes emerged from the data. The main themes were as follows: mothers' experiences of jaundice crises and its management, and mothers' present experiences after crisis of jaundice. First theme arranged into four subthemes and second theme was grouped into three subthemes. Conclusion: Mothers' and grandmothers' cultural and dietary beliefs have an important impact on mothers' health-seeking behavior. Educational programs about neonatal jaundice and its management through prenatal care consulting and mass media is recommended as an important priority for health system of country.